Molecular diversity of phospholipase D in angiosperms - Eliás, Marek; Potocký, Martin; Cvrcková, Fatima; Zárský, Viktor (BMC genomics, 2002)
BACKGROUND: The phospholipase D (PLD) family has been identified in plants by recent molecular studies, fostered by the emerging importance of plant PLDs in stress physiology and signal transduction. However, the presence of multiple isoforms limits the power of conventional biochemical and pharmacological approaches, and calls for a wider application of genetic methodology. RESULTS: Taking advantage of sequence data available in public databases, we attempted to provide a prerequisite for such an approach. We made a complete inventory of the Arabidopsis thaliana PLD family, which was found to comprise 12 distinct genes. The current nomenclature of Arabidopsis PLDs was refined and expanded to include five newly described genes. To assess the degree of plant PLD diversity beyond Arabidopsis we explored data from rice (including the genome draft by Monsanto) as well as cDNA and EST sequences from several other plants. Our analysis revealed two major PLD subfamilies in plants. The first, designated C2-PLD, is characterised by presence of the C2 domain and comprises previously known plant PLDs as well as new isoforms with possibly unusual features catalytically inactive or independent on Ca2+. The second subfamily (denoted PXPH-PLD) is novel in plants but is related to animal and fungal enzymes possessing the PX and PH domains. CONCLUSIONS: The evolutionary dynamics, and inter-specific diversity, of plant PLDs inferred from our phylogenetic analysis, call for more plant species to be employed in PLD research. This will enable us to obtain generally valid conclusions.